Joy, the summer vacation fairy - Meadows, Daisy; Ripper, Georgie (New York : Scholastic, 2007)
Joy and the other fairies try to keep Jack Frost from ruining the vacation atmosphere of Rainspell Island.
"A Little Apple paperback."
RL2.
006-009.
Keywords: Jack Frost -- (Legendary character) -- Juvenile fiction; Fairies -- Juvenile fiction; Vacations -- Juvenile fiction; Summer -- Juvenile fiction; Islands -- Juvenile fiction; Fairies -- Fiction; Vacations -- Fiction; Islands -- Fiction; Jack Frost -- Fiction; Fantasy; Fantasy fiction